Effect of 2-D nanomaterials on sensitivity of plasmonic biosensor for efficient urine glucose detection - Yadav, Archana; Kumar, Shatrughna; Kumar, Anil; Sharan, Preeta (Frontiers in Materials, 2023)
This paper presents a multi-layered Kretschmann configuration-based Surface Plasmon Resonance (SPR) biosensor for the detection of urine glucose. The modelling, simulation, and analysis have been done by using Silver (Ag) and Gold (Au) layer on the low refractive index prism BK-7 separately, which created two structures: structure-I (BK7/Ag/Bio-sample) and structure-II (BK7/Au/Bio-sample). Urine samples from a non-diabetic person (0–15 mg/dL) and a diabetic person (.625 gm/dL, 1.25 gm/dL, 2.5 gm/dL, 5 gm/dL, and 10 gm/dL) with the corresponding refractive indices of 1.335, 1.336, 1.337, 1.338, 1.341, and 1.347, respectively, have been used as a bio-sample that has been put on the top layer of the sensor. An investigation was conducted to improve the performance parameters of the proposed plasmonic biosensor by layering different 2-D nanomaterials (graphene, BP) and TMDC materials (MoS2, MoSe2, WS2, and WSe2) over the silicon (Si) layer in both structures at a visible wavelength of 633 nm, using Transfer Matrix Method (TMM). With layer thickness optimization, Structure-I (BK7/Ag (56 nm/Si (3 nm)/WS2 (.8 nm)/Bio-sample) shows a sensitivity of 200 °/RIU which is enhanced up to 1.7 times that of the conventional biosensor (BK7/Ag/Bio-sample) and 1.3 times that of the BK7/Ag (56 nm)/Si (3 nm)/Bio-sample based biosensor. Whereas in Structure-II (BK7/Au (50 nm)/Si (3 nm)/BP (.53 nm)/Bio-sample) with optimised layer thickness, we obtained a sensitivity of 273.4°/RIU, which is enhanced up to 2.2 times that of the conventional biosensor (BK7/Au/Bio-sample) and 1.3 times that of the BK7/Au (50 nm)/Si (3 nm)/Bio-sample. Other performance parameters such as detection accuracy for Structure-I and Structure-II are .5617 degree−1 and .134 degree−1 respectively. The Figure of merit for Structure-I and Structure-II are 112.35/RIU and 36.89/RIU respectively. Therefore, we expect Structure-I (BK7/Ag (56 nm/Si (3 nm)/WS2 (.8 nm)/Bio-sample) and Structure-II (BK7/Au (50 nm)/Si (3 nm)/BP (.53 nm)/Bio-sample) have the potential to detect the glucose concentration with quick response and high sensitivity in terms of the resonance angle shift in SPR curves.